(3eNJUQ GdRjL GdEjdNGfis - (3CHi GdYHGSj CMeO Hf EHQGgje Hf edGYH GdSQejfis; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3bGd CHh GdYHGSj GdSQejfi CeG HYO , aEfg deG cGf GdUOQ GdeMbb GdWhSi QCjJ Cf GNJUQ CHhGH RjLI GdeSei HGdEjdNGfi eGdGHO efg s
(3BNQgG (B:s
(3aai Pdc Gdjhe XghQ GdchcH ef JMH GdTYGY Ch ENaGFg dCjgeG hEf GNJda bSefG GdaVd HjfgeG hgPG GdLOhd s
(3HBNQgG LOGhd cKjQIs
(3HgG HYV WeSs
(3cJHJ Hbde ajg VHWs
(3HChdgG Jedc dGHQGgje GdeYQha H` GHf LGaQ hgh Gdehba HLGeY GdLGhdi HZRI SfI (B828 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
Keywords: (3Gdadcs